The Implementation of Two Strength Method on the Topic of Chemical Equilibrium toward Learning Outcomes of Students in 11th Grade Science at SMA Negeri 1 Sindue on Academic Year 2016-2017 - Andi Pangeran; Irwan Said; Sri M. Sabang (Universitas Tadulako, 2020)
This study aimed to determine the differences of students’ learning outcomes between the class implementing the two strenght method and the class with the lecture method on the topic of chemical equilibrium in 11th grade science at SMA Negeri 1 Sindue on academic year 2016-2017. This type of study was a quasi experiment with a non-randomized pretest-posttest control group design. The sample of this study consisted of two classes namely students of class XI science 3 as the exsperimental class (n = 30) and students of class Xl science 2 as the control class (n = 30). Data of students’ learning outcomes were analyzed using t-test statistic of two-party. The analysis obtained the everage scores of the experimental and the control class were 50.50 with a standard deviation of 9.79 and 41.03 with a standard deviation of 11.01. Result of the hypothesis test with t-test statistic of two-party obtained –ttable ≤ tcount ≥ + ttable (tcount = 2.35 and ttable = 2.00) with a significance level of 0.05 and degree of freedom of 58 then H0 was rejected and H1 was accepted. This study concludes that there is difference in students’ learning outcomes between class with the implementation of the two strength methods and class with the lecture method on the topic of chemical equilibrium in 11th grade science at SMA Negeri 1 Sindue on academic year 2016-2017.